2021
DOI: 10.3389/fimmu.2021.623280
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Epithelial Cell-Derived IL-15 and IL-15 Receptor α Chain Foster Local Environment for Type 1 Innate Like T Cell Development

Abstract: Expression of tissue-restricted antigens (TRAs) in thymic epithelial cells (TECs) ensures negative selection of highly self-reactive T cells to establish central tolerance. Whether some of these TRAs could exert their canonical biological functions to shape thymic environment to regulate T cell development is unclear. Analyses of publicly available databases have revealed expression of transcripts at various levels of many cytokines and cytokine receptors such as IL-15, IL-15Rα, IL-13, and IL-23a in both human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 75 publications
2
1
0
Order By: Relevance
“…In addition, besides iNKT cells, we also found that γδT1 cells, which are a small population of thymocytes, were modestly decreased in FoxN1-Cre IL-15 cKO mice (fig. S3, D and E), consistent with a recent report ( 22 ). To exclude any influence from γδT1 cells, we analyzed FoxN1-Cre IL-15 cKO × TCRδ KO mice.…”
Section: Resultssupporting
confidence: 92%
“…In addition, besides iNKT cells, we also found that γδT1 cells, which are a small population of thymocytes, were modestly decreased in FoxN1-Cre IL-15 cKO mice (fig. S3, D and E), consistent with a recent report ( 22 ). To exclude any influence from γδT1 cells, we analyzed FoxN1-Cre IL-15 cKO × TCRδ KO mice.…”
Section: Resultssupporting
confidence: 92%
“…The FoxN1-Cre IL-15 conditional knockout (cKO) mice, deficient in IL-15 expression in mTECs, were utilized to elucidate the thymic IL-15 niche for iNKT cells. The FoxN1-Cre IL-15 cKO mice exhibit a reduction in NKT1 cells, but not NKT2 or NKT17 cells, which aligns with a preceding study confirming the indispensability of TEC-derived IL-15 for type 1 innate-like T cells, including iNKT cells ( 92 ). Subsequently, mature stage 3 iNKT cells, which are nearly identical to NKT1 cells in mice, can be classified into three subpopulations based on the presence of the NK cell receptor CD244 (also known as 2B4 or SLAMF4) and the chemokine receptor CXCR6: CD244 + CXCR6 + double-positive C2 iNKT cells, CD244 − CXCR6 + single-positive C1 iNKT cells, and CD244 − CXCR6 − double-negative C0 iNKT cells ( 11 ).…”
Section: Thymic Il-15 Niche-dependent Circulating Inkt Cellssupporting
confidence: 89%
“…1E ). Previous studies have demonstrated that IL-7 and IL-15 produced by TECs regulate the development of thymocytes and innate lymphoid cells ( 28 29 ). Based on these results, it is reasonable to hypothesize that the decreased cytokine signaling in old age TECs may contribute to the development of these subsets.…”
Section: Resultsmentioning
confidence: 99%